Hemophagocytic lymphohistiocytosis: a clinical overview and case study - Fatima, Zohra; Bhaganagare, Vivek Vijayrao; Mohammed, Owaise; Amjad, Mariyah; Siddiqua, Syeda Ayesha (International Journal of Research in Medical Sciences, 2025)
Hemophagocytic lymphohistiocytosis (HLH) is a rare, potentially life-threatening hyperinflammatory syndrome resulting from excessive immune activation. It is broadly classified into primary (genetic) and secondary (acquired) forms, with secondary HLH often triggered by infections, malignancies, or autoimmune diseases. The condition presents significant diagnostic challenges due to overlapping features with other systemic inflammatory disorders and sepsis. This report describes a pediatric case of HLH associated with a bacterial infection, highlighting the importance of timely diagnosis and treatment to improve outcomes. A 9-year-old female presented with persistent fever, abdominal pain, distension, facial edema, hepatosplenomegaly, and pancytopenia. Laboratory investigations revealed hyperferritinemia (18,500 ng/ml), hypertriglyceridemia (450 mg/dl), and hypofibrinogenemia (1.2 g/l). Bone marrow aspirate demonstrated hemophagocytosis. Blood cultures identified Klebsiella pneumoniae as the infectious trigger. The patient met six of the eight HLH-2009 diagnostic criteria, confirming the diagnosis of secondary HLH. Treatment included intravenous dexamethasone and immunoglobulin (IVIG), along with supportive care. The patient responded well, with clinical improvement and normalization of laboratory parameters. Genetic evaluation was done to exclude primary HLH and it turned out to be PRF1 gene. This case underscores the critical need for early recognition of HLH in patients presenting with fever, cytopenias, and elevated inflammatory markers. Adherence to established diagnostic criteria and prompt initiation of treatment are essential to improving survival in this severe condition. The case also highlights the role of multidisciplinary care and genetic testing in ensuring optimal long-term management.